2020
DOI: 10.1002/term.3005
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing grafts: Omega‐3 fatty acid lipid content differentiates the lipid profiles of acellular Atlantic cod skin from traditional dermal substitutes

Abstract: Acellular fish skin (ACS) has emerged as a dermal substitute used to promote wound healing with decreased scar formation and pain relief that may be due to polyunsaturated fatty acid (PUFA) content. However, the PUFA content of ACS is still unknown. The aim of this study was to compare the total fatty acids and lipid profiles of ACS to two bovine‐based grafts and standard of care human cadaver skin (HCS). Furthermore, there was also the goal to assess the capability of ACS lipid content to enhance wound healin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…C18 SM (d18:1/18:0) and C18 ceramide (d18:1/18:0) were run alongside samples for reference as both SMs and ceramides have consistently been associated with AD [ 54 ]. Ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS) lipidomic analysis was carried out as described in Kotronoulas et al [ 55 ]. The analytical instrumentation used was an ACQUITY UPLC system (UPLC ACQUITY, Waters Corporation, Milford, MA) coupled to a traveling-wave ion mobility (IMS) qTOF mass spectrometer (Synapt G2 HDMS, Waters Corporation, Manchester, UK).…”
Section: Methodsmentioning
confidence: 99%
“…C18 SM (d18:1/18:0) and C18 ceramide (d18:1/18:0) were run alongside samples for reference as both SMs and ceramides have consistently been associated with AD [ 54 ]. Ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS) lipidomic analysis was carried out as described in Kotronoulas et al [ 55 ]. The analytical instrumentation used was an ACQUITY UPLC system (UPLC ACQUITY, Waters Corporation, Milford, MA) coupled to a traveling-wave ion mobility (IMS) qTOF mass spectrometer (Synapt G2 HDMS, Waters Corporation, Manchester, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Based on our previous observations, [19] both EPA and DHA of the FSG lipid content are principally part of phosphatidylcholines and hence these alterations indicate the enzymatic release of ω3-FA by phospholipases, allowing secretion and further metabolism within the wound.…”
Section: Discussionmentioning
confidence: 86%
“…[18] In a recent study, our group demonstrated that FSG is particularly rich in phosphatidylcholines that contain EPA or DHA and that this differentiates FSG from other skin grafting materials. [19] Thus, it has been postulated that the use of ω3-FA enriched scaffold biomaterials can be an effective way to topically deliver ω3-FA to wounds and enhance the healing processes via resolution of inflammation. The goal of the present study was to explore whether the FSG derived ω3-FA can alter the formation of lipid mediators during burn wound healing, as opposed to other grafts of mammalian origin that are not rich in ω3-FA.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-performance liquid chromatography (UPLC) (Acquity, Waters, Manchester, UK) was coupled with a quadrupole-time of flight mass spectrometer (Synapt G2, Waters, Manchester, UK). For the lipid samples, chromatographic separation was achieved as previously described [19].…”
Section: Uplc-msmentioning
confidence: 99%
“…Ultra-performance liquid chromatography (UPLC) (Acquity, Waters, Manchester, UK) was coupled with a quadrupole-time of flight mass spectrometer (Synapt G2, Waters, Manchester, UK). For the lipid samples, chromatographic separation was achieved as previously described [19]. For the metabolomic samples, chromatographic separation was achieved by hydrophilic interaction liquid chromatography (HILIC) using an Acquity amide column, 1.7 µm pooled QC samples to equilibrate the system; calibrators; samples and spiked pooled QC samples; calibrators.…”
Section: Uplc-msmentioning
confidence: 99%